Graphene Oxide/BiOCl Nanocomposite Films as Efficient Visible Light Photocatalysts - Lin, Weitian; Yu, Xiang; Zhu, Yi; Zhang, Yuanming (Frontiers in Chemistry, 2018)
A novel graphene oxide/BiOCl (GO/BiOCl) nanocomposite film was prepared via a spread coating method. In visible-light photocatalytically degrading Rhodamine B (RhB) experiments, 2 wt% GO/BiOCl could degrade 99% of RhB within 1.5 h and the rate constant was 12.2 times higher than that of pure BiOCl. The degradation efficiency still kept at 80% even after 4 recycles, evidencing the relatively good recyclability. The enhancement was attributed to the improvement of visible light adsorption and charge separation. Holes and superoxide radicals•O2– played a major role as reactive species. The values of conduction band and valence band for GO and BiOCl were calculated and a new photocatalytic mechanism of GO/BiOCl nanocomposite was proposed.